Relationship Between Social Responsibility and Financial Performance: Evidence from Indonesia - Destiya Dwi Ambarwati; Mulianto Mulianto; Vinenda Juane Takasanakeng; Weismann Immanuel Sigalingging (Syntax Corporation Indonesia, 2022)
This empirical theoretical study investigates the two-way relationship between corporate social responsibility and financial performance in Indonesian businesses. The theoretical underpinning for the conceptual model is based on agency, stewardship, resource reliance, and stakeholder theory. The social behavior index is made up of four components: participation in global reporting initiatives, inclusion of Green Index firms, good compliance, Corporate Governance Recommendations, and signatories to the Global Compact. The study's findings reveal a positive relationship in both directions: social benefits and positive feedback that social policies increase financial resources. Increased financial success, on the other hand, boosts the social and economic benefits of enacting rules that encourage board-level components to seriously consider spending more money. As a result, this research motivates social behavior members to contribute globally to the betterment of society